Beyond the Classroom: The Potential of Project-Based Learning and YouTube in Fostering Learning Engagement and Creativity in Digital Learning - Putri, Elviza Yeni; Oktarina, Rahmi; Sidiqi, Adam Rasyid; Saputra, Indra (AI Society & STMIK Indonesia, 2024)
The background of this research is the low of student learning engagement and creativity. The purpose of this study is to analyze the potential of project-based learning and YouTube in enhancing learning engagement and creativity. The method used in this research is a semi-systematic literature review. The results of the study describe that project-based learning and the YouTube platform have the potential to increase learning engagement and creativity. Some potential aspects of project-based learning integrated with YouTube include relevant and interesting learning content, real project learning experiences, interactive and responsive platforms, flexibility and adaptability, online collaboration features, experimental activity opportunities, and constructive feedback. The findings of this research can be considered by educators when designing learning experiences aimed at improving student learning engagement and creativity. Further research recommendations include the need for experimental implementation of project-based learning integrated with YouTube and measuring the impact of treatment in increasing learning engagement and creativity.